Tinjauan Keadaan Sanitasi Pasar di Pasar Umum Kusamba Desa Kusamba Kecamatan Dawan Kabupaten Klungkung - Rusiana Putri Candra Ni Made; I Wayan Suarta Asmara; i Wayan Sudiadnyana (Poltekkes Kemenkes Denpasar, 2019)
Abstrack: Sanitation of public places is a public health problem that is quite urgent, because the public place is a meeting place of all kinds of society with all sickness. Public places or facilities must carry out environmental sanitation, among others, places that facilitate the occurrence of disease transmission, or public service places where the intensity of the number and timing of visits is high. Place or public facilities one of the market. Kusamba General Market is located at Amlapura Highway, Kusamba Village, Dawan District with 2.974 m2 of land area consisting of 227 traders. The purpose of this research is to know the condition of market sanitation in Kusamba General Market Kusamba Village Dawan Year 2018. This research use descriptive method with data collection technique using observation sheet. Result of research to market building get category enough with score 16, market sanitation get category enough with score 12, security got by category less with score 1. Total of whole state of sanitation market that is enough with score 28. It is suggested to market manager to pay more attention to cleanliness the market environment and adding sanitation facilities. To the traders to jointly maintain market facilities and market hygiene. To the government or related institutions located in the working area of Pasar Umum Kusamba to conduct supervision / inspection of market sanitation and health of traders.